Experimental modal analysis of British rock lighthouses - Brownjohn, James Mark William; Raby, Alison; Bassitt, James; Antonini, Alessandro; Hudson, Emma; Dobson, Peter (Marine structures, 2018)
Iconic lighthouses constructed on offshore reefs around the British Isles in the 19th century continue to play a crucial role in safe navigation, but the longevity of these historical structures is threatened by extreme weather. A program of experimental dynamic investigations has been carried out to support characterisation of extreme impulsive breaking wave loads on these structures, using monitored response data. This paper describes the procedures and outcomes of this program, which included modal tests of a collection of six of these lighthouses between June 2016 and October 2017. Five of the six lighthouses tested (Les Hanois, Wolf Rock, Longships, Bishop Rock and Eddystone) feature a 20th century metal helideck atop a 19th century masonry tower, with a Scottish lighthouse (Dubh Artach) being the exception that provides baseline behaviour of a relatively simple tower. All the masonry towers are imperfectly axisymmetric to some degree and all present logistical challenges for experimental work as they can only be accessed by helicopter flights subject to severe weather and time constraints. Against such challenges it was possible to identify key modal parameters, and to highlight some interesting effects due to symmetry and helideck retrofit. Notable findings were that most important modes have frequencies ranging between 4 Hz and 7 Hz and modal masses as low as ∼200 t. The rarely investigated effect of imperfect axisymmetry on forced vibration testing is studied, along with the introduction of additional modes due to retrofitted helideck. The implications of these effects on experimental modal analysis from forced vibration test data is illustrated. Finally, accelerations recorded on Wolf Rock Lighthouse during the 2017–2018 winter storm season show the modal test data can be used to infer breaking wave modal impulses up to 8 kNs. •A unique exercise on modal testing of a class of structures that provide significant logistical challenges is presented.•Surprisingly, forced vibration testing during strong winds provided more usable data than ambient vibration testing.•Vibration modes are aligned weakly with specific directions, which there was some success at identifying.•Simple simulations explain directional affects on frequency response functions and mode splitting due to a helideck.•Monitoring data facilitated characterising the extreme impulsive wave loads, some at similar levels to a large earthquake.